Revitalisasi Nilai-Nilai Kearifan Lokal dalam Pembelajaran Sejarah: Pelatihan Guru SMA di Maluku Tengah tentang Peran Kewang dan Praktik Sasi - Pattiasina, Johan; Wattimury, Samuel Michael; Harnisa, Susi (Jurnal Pengabdian Arumbai, 2025)
This community service was conducted in Haruku Village, Central Maluku Regency, based on the urgency of revitalizing local wisdom values of kewang and sasi practices within high school history learning. The activity aimed to enhance history teachers’ competence in integrating local cultural values into contextual education linked to community traditions. A participatory-collaborative approach was employed through training, workshops, mentoring, and continuous evaluation. The results showed improvement in teachers’ ability to design local-based teaching modules, established partnerships between schools and traditional institutions, and strengthened community awareness of cultural preservation. The activity demonstrated the synergy between education, culture, and society as a sustainable empowerment model. The recommendation emphasizes regional policy support for replicating similar programs across other Maluku regions.